Avaliação da atenção pré-natal em dois serviços de saúde da 4ª Coordenadoria Regional de Saúde do Rio Grande do Sul - Fonseca, Hendil Fortes da (2024)
Every pregnant woman needs quality care according to the characteristics of the pregnancy and its complications. Thus, both Primary Health Care and regional referral services become of great importance for monitoring pregnancies and maternal and perinatal outcomes. In addition, quality prenatal care is necessary to direct the flow and provide adequate guidance for gestational risks. Thus, these services need to monitor the results of the medical interventions to which these patients are subjected. The objective of this study was to evaluate the quality of prenatal care, the epidemiological profile, the evolution, the outcome and the complications of pregnancies monitored in two prenatal services of the 4th Regional Health Coordination of Rio Grande do Sul (CRS-RS), in the municipality of Agudo, at the Basic Health Unit (UBS) and in the municipality of Santa Maria, at the University Hospital of Santa Maria (HUSM). Quantitative, cross-sectional, descriptive and exploratory research, involving pregnant women attended at the 4th CRS-RS, in the municipalities of Agudo, with normal-risk pregnant women and Santa Maria with high-risk pregnant women, between 2020 and 2022 in a retrospective manner, with review of medical records. A total of 1489 pregnant women participated in the study, 1298 from HUSM and 191 from the municipality of Agudo, with an average age between 19 and 34 years. The services evaluated had a statistical difference in the number of previous cesarean sections (p<0.001). Among the risk factors, there was a significant difference (p value <0.001) in the percentage of pregnant women with hypertension, in HUSM 635 (48.9%) presented versus 16% in the usual risk prenatal, with Diabetes mellitus, in HUSM it was 40.3% and versus 16% of the Agudo sample, with previous Systemic Arterial Hypertension, being 10.7% of pregnant women in HUSM and 3.1% in Agudo. Furthermore, previous HAS was 10.7% of pregnant women in HUSM and 3.1% in Agudo, with a significant difference between the services. The data also showed that 1463 (99.2%) did not present any fetal death, an important outcome to be analyzed, with no significant difference between the services. Furthermore, approximately 10% of newborns in the tertiary service required admission to a neonatal ICU, compared to approximately 2% of those in the municipality of Agudo, who received prenatal care for normal risk and high-risk infants. This study concluded that prenatal care for normal risk and high-risk infants in the interior of the state had characteristics according to their level of complexity, and most maternal-fetal outcomes were similar, among which fetal death stands out, being similar in both services. In short, the importance of effective coordination in health networks is highlighted, in order to refer appropriately and in time for the management of risk factors and comorbidities in a reference service.